Causality in Islamic philosophy : the arguments of Ibn Sina - Ariff, Syamsuddin (Expanded Academic ASAP, 2009)
Few ideas in the history of philosophy in Islam have been so much debated, attacked, and defended as has the thesis that a necessary connection exists between cause and effect, that cause and effect are so inextricably linked that the existence of one necessitates and implies that of the other, and that if the cause has occurred, the effect cannot fail to occur. For instance, it is this conception of causality, with its hidden assumptions and far-reaching ramifications (e.g. the fettering of God's Will, the eternity of the world, the denial of the possibility of miracles, etc.), that prompted al-Ghazali (d. 505/1111) to charge Ibn Sina with heresy and infidelity. This article reexamines Ibn Sina's views on this crucial issue by looking first into his exposition of the four causes and his account of causal efficacy and necessity, before finally discussing his theory of chance.